Interventions to Improve Adherence in Patients with Immune-Mediated Inflammatory Disorders: A Systematic Review. - Fanny Depont; Francis Berenbaum; Jérome Filippi; Michel Le Maitre; Henri Nataf; Carle Paul; Laurent Peyrin-Biroulet; Emmanuel Thibout (PLoS ONE, 2015)
Background In patients with immune-mediated inflammatory disorders, poor adherence to medication is associated with increased healthcare costs, decreased patient satisfaction, reduced quality of life and unfavorable treatment outcomes. Objective To determine the impact of different interventions on medication adherence in patients with immune-mediated inflammatory disorders. Design Systematic review. Data sources MEDLINE, EMBASE and Cochrane Library. Study eligibility criteria for selecting studies Included studies were clinical trials and observational studies in adult outpatients treated for psoriasis, Crohn's disease, ulcerative colitis, rheumatoid arthritis, spondyloarthritis, psoriatic arthritis or multiple sclerosis. Study appraisal and synthesis methods Intervention approaches were classified into four categories: educational, behavioral, cognitive behavioral, and multicomponent interventions. The risk of bias/study limitations of each study was assessed using the GRADE system. Results Fifteen studies (14 clinical trials and one observational study) met eligibility criteria and enrolled a total of 1958 patients. Forty percent of the studies (6/15) was conducted in patients with inflammatory bowel disease, half (7/15) in rheumatoid arthritis patients, one in psoriasis patients and one in multiple sclerosis patients. Seven out of 15 interventions were classified as multicomponent, four as educational, two as behavioral and two as cognitive behavioral. Nine studies, of which five were multicomponent interventions, had no serious limitations according to GRADE criteria. Nine out of 15 interventions showed an improvement of adherence: three multicomponent interventions in inflammatory bowel disease; one intervention of each category in rheumatoid arthritis; one multicomponent in psoriasis and one multicomponent in multiple sclerosis. Conclusion The assessment of interventions designed for increasing medication adherence in IMID is rare in the literature and their methodological quality may be improved in upcoming studies. Nonetheless, multicomponent interventions showed the strongest evidence for promoting adherence in patients with IMID.